2018
DOI: 10.1016/j.celrep.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Potency Analysis of Mesenchymal Stromal Cells Using a Combinatorial Assay Matrix Approach

Abstract: SUMMARY Assays that can characterize MSC immune potency need to be identified for use in advanced clinical trials. MSCs possess a number of putative regenerative and immunomodulatory properties, and an assay matrix approach may best capture involved effector pathways. We have tested two assay systems to measure the potency of MSCs derived from human subjects: MSC secretome analysis and a quantitative RNA-based array for genes specific to immunomodulatory and homing properties of MSCs. Secretome analysis identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 48 publications
3
178
0
2
Order By: Relevance
“…In terms of MSC function, on which the MSC clinical application were theoretically based, the DEGs upregulated in subpopulations C3 were enriched in extracellular structure organization, developmental process, and muscle contraction, while DEGs upregulated in subpopulations C4 were associated with immunomodulation function (Figure 4A). Secretome analysis revealed that increased levels of some cytokines, such as CCL2, GCSF, VEGF, and IL-7, are positively correlated with immunosuppression (Chinnadurai et al, 2018). Among these subpopulation, expression levels of CCL2 and CSF3 are highest in C4 subpopulation (Figure S6F), implicating its immunomodulation therapeutic potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of MSC function, on which the MSC clinical application were theoretically based, the DEGs upregulated in subpopulations C3 were enriched in extracellular structure organization, developmental process, and muscle contraction, while DEGs upregulated in subpopulations C4 were associated with immunomodulation function (Figure 4A). Secretome analysis revealed that increased levels of some cytokines, such as CCL2, GCSF, VEGF, and IL-7, are positively correlated with immunosuppression (Chinnadurai et al, 2018). Among these subpopulation, expression levels of CCL2 and CSF3 are highest in C4 subpopulation (Figure S6F), implicating its immunomodulation therapeutic potential.…”
Section: Resultsmentioning
confidence: 99%
“…VEGFA , and other two cytokines, CXCL5 and CXCL8 (IL-8), were required for the angiogenic activity of MSCs and have been selected as an assay matrix for angiogenic potency assay for MultiStem product (Galipeau et al, 2016; Lehman et al, 2012). Furthermore, in vitro co-culture assays demonstrated that the increased levels of VEGFA and chemokine CCL2 in MSCs were positively correlated with PBMC suppression (Chinnadurai et al, 2018). Chemokines, a family of small cytokines, are recognized as key mediators of MSCs migration and immunosuppression (Hocking, 2015; Ren et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several molecules such as interleukin-10 (Jiao et al, 2011), prostaglandin E-2 (Solchaga and Zale, 2012), and IDO (Tomchuck et al, 2008Waterman et al, 2010) have been examined to suggest potency of MSC, but given the robust secretory repertoire of MSC, a singular molecular assessment is inadequate. In this study and several others (Chinnadurai et al, 2018;Jiao et al, 2011), potency corresponded to diminished proliferation of stimulated immune cells when co-cultured with BM-MSC (Chinnadurai et al, 2018;Scruggs et al, 2013), further analyzing specific subsets of PBMC and T cells to determine immunomodulatory potency yielded more compelling implications.…”
Section: Immunomodulatory Potency Of Unf Primed Bm-msc Mitigated Pbmcmentioning
confidence: 73%
“…5A, B). Thus, we found that MSCs immunomodulatory phenotype cannot be captured using a single surrogate marker, in this case IDO, highlighting the need for multiple metrics to be used to predict MSC function 33 . In addition, while we initially thought the dose and duration of pre-licensing would be the most critical parameters to optimize, we found the donor itself had the largest influence on the potency of PL-MSCs.…”
Section: Mscsmentioning
confidence: 99%